How can parent education be used as a resource to improve and promote healthy relationships with children? - Brittany J Riggins (Adult Education Research Conference, 2017)
From my observations I realized that if parents used education as a resource to educate themselves on how to communicate and use the knowledge acquired through parenting courses maybe relationships with their children would be less strained.
Keywords: Parent; Education; Low-Income